Surface detail reproduction and dimensional stability of contemporary irreversible hydrocolloid alternatives after immediate and delayed pouring - Preethi Kusugal; Ritu Sunil Chourasiya; Zarir Ruttonji; Preeti Astagi; Ajay Kumar Nayak; Abhishekha Patil (Wolters Kluwer Medknow Publications, 2018)
Purpose: To overcome the poor dimensional stability of irreversible hydrocolloids, alternative materials were introduced. The dimensional changes of these alternatives after delayed pouring are not well studied and documented in the literature. The purpose of the study is to evaluate and compare the surface detail reproduction and dimensional stability of two irreversible hydrocolloid alternatives with an extended-pour irreversible hydrocolloid at different time intervals. Materials and Methods: All testing were performed according to the ANSI/ADA specification number 18 for surface detail reproduction and specification number 19 for dimensional change. The test materials used in this study were newer irreversible hydrocolloid alternatives such as AlgiNot FS, Algin-X Ultra FS, and Kromopan 100 which is an extended pour irreversible hydrocolloid as control. The surface detail reproduction was evaluated using stereomicroscope. The dimensional change after storage period of 1 h, 24 h, and 120 h was assessed and compared between the test materials and control. The data were analyzed using one-way ANOVA and post hoc Bonferroni test. Results: Statistically significant results (P < 0.001) were seen when mean scores of the tested materials were compared with respect to reproduction of 22 μm line from the metal block. Kromopan 100 showed statistically significant differences between different time intervals (P < 0.001) and exhibited more dimensional change. Algin-X Ultra FS proved to be more accurate and dimensionally stable. Conclusions: Newer irreversible hydrocolloid alternative impression materials were more accurate in surface detail reproduction and exhibited minimal dimensional change after storage period of 1 h, 24 h, and 120 h than extended-pour irreversible hydrocolloid impression material.